The Differentiation Potential of Apical Papilla Cells in Relation to Tenascin-C and Syndecan-1 Expression and Their Potential Role in Regeneration - K. Kodonas; A. Fardi; S. Papadimitriou; C. Gogos (International Journal of Dentistry)
Conclusions: Cell differentiation potential in the developing swine apex is progressively restricted to the newly formed dental pulp, whereas phenotypic expression of apical papilla cells remains undetermined unless the new microenvironment triggers cell differentiation towards the odontoblastic lineage.